Analysis of the implementation of good governance principles in the mandatory B30 biodiesel program in Indonesia - Surya Tarmiani (Integritas: Jurnal Antikorupsi, 2026)
The mandatory biodiesel policy is one of the Indonesian government's main strategies to achieve the 23% renewable energy mix target by 2025 and reduce greenhouse gas emissions. However, the biodiesel subsidy policy faces challenges such as potential inefficiency, lack of transparency, and corruption risks. This study aims to analyze the implementation of good governance principles in the mandatory B30 biodiesel program and identify influencing factors. The study was conducted using a qualitative approach through in-depth interviews with sources from the Ministry of Energy and Mineral Resources, BPDPKS, Aprobi, and a review of regulatory documents and audit reports. The results show that although the B30 program provides significant benefits in terms of foreign exchange savings, domestic CPO absorption, and emission reductions, weaknesses remain in aspects of accountability, transparency in market index pricing, and the imposition of sanctions on business entities that do not meet distribution quotas. This study's recommendations include increasing the transparency of the biodiesel HIP formula, strengthening the subsidy distribution verification mechanism, and imposing strict sanctions to encourage business entity compliance. This research contributes to the energy governance literature and can serve as a reference for the formulation of more effective and sustainable biodiesel subsidy policies.